Expression of a homologously recombined erythopoietin-SV40 T antigen fusion gene in mouse liver: evidence for erythropoietin production by Ito cells. - Maxwell, P; Ferguson, D; Osmond, M; Pugh, C; Heryet, A; Doe, BG; Johnson, M; Ratcliffe, P (1994)
We have obtained transgenic mice in which an erythropoietin-SV40 virus T antigen fusion gene is homologously recombined into the native Epo locus. This gene is expressed in a tissue-specific manner closely resembling that of the native Epo gene. Immunohistochemical detection of SV40 T antigen has been used to characterize the hepatic cell populations expressing the transgene. In mice stimulated by anaemia or hypobaric hypoxia, SV40 T antigen was demonstrated in two liver cell populations: a subset of hepatocytes and a nonparenchymal cell type. Immunohistochemical and ultrastructural characterization of these cells by light and electron microscopy showed the nonparenchymal cell type to be the Ito cells, which lie in a persinusoidal position within the space of Disse. We therefore conclude that Ito cells are the nonhepatocytic source of liver Epo production. These cells show many similarities to the Epo-producing fibroblastoid interstitial cells of the kidney.